In situ observations of the reversible vacancy ordering process in van der Waals-bonded Ge–Sb–Te thin films and GeTe–Sb2Te3 superlattices. Issue 22 (28th May 2019) - Lotnyk, Andriy; Dankwort, Torben; Hilmi, Isom; Kienle, Lorenz; Rauschenbach, Bernd
Abstract : Reconfiguration of the structural order in layered Ge–Sb–Te structures is associated with the formation of vacancy layers and readjustment of interplanar spacing. Abstract : Chalcogenide-based thin films are employed in data storage and memory technology whereas van der Waals-bonded layered chalcogenide heterostructures are considered to be a main contender for memory devices with low power consumption. The reduction of switching energy is due to the lowering of entropic losses governed by the restricted motion of atoms in one dimension within the crystalline states. The investigations of switching mechanisms in such superlattices have recently attracted much attention and the proposed models are still under debate. This is partially due to the lack of direct observation of atomic scale processes, which might occur in these chalcogenide systems. This work reports direct, nanoscale observations of the order–disorder processes in van der Waals bonded Ge–Sb–Te thin films and GeTe–Sb2 Te3 -based superlattices using in situ experiments inside an aberration-corrected transmission electron microscope. The findings reveal a reversible self-assembled reconfiguration of the structural order in these materials. This process is associated with the ordering of randomly distributed vacancies within the studied materials into ordered vacancy layers and with readjustment of the lattice plane distances within the newly formed layered structures, indicating the high flexibility of these layered chalcogenide-based systems. Thus, the ordering process results in the formation of vacancy-bonded building blocks intercalated within van der Waals-bonded units. Moreover, vacancy-bonded building blocks can be reconfigured to the initial structure under the influence of an electron beam, while in situ exposure of the recovered layers to a targeted electron beam leads to the reverse process. Overall, the outcomes provide new insights into local structure and switching mechanism in chalcogenide superlattices.